Use of repurposed and adjuvant drugs in hospital patients with COVID-19: multinational network cohort study - Prats Uribe, A; Sena, AG; Lai, LYH; Ahmed, W; Morgado Areia, C; Shah, K; Lane, J; Burn, E; Prieto Alhambra, D (BMJ Publishing Group, 2021)
Objective: To investigate the use of repurposed and adjuvant drugs in patients admitted to hospital with covid-19 across three continents.